Aeration system efficiency of the cascades in the coffee wastewater treatment - Eustáquio Júnior, Valdeir; Teixeira de Matos, Antonio; Alfonsa Vieira Lo Monaco, Paola; Pimentel de Matos, Mateus (Coffee Science - ISSN 1984-3909, 2014)
The issue of this work was to assess the efficiency of aeration systems in cascades for the treatment of wastewater from the processing of coffee fruits. The aeration system was installed in cascades of a level difference of 4.14 m from the ground with 23 steps (height, width and length of 0.18, 0.32 and 0.60 m, respectively.) Samples of influent and effluent, after system operating with three recirculations per day, over a period of 10 days, were analyzed. The average removal efficiency of COD was 28.9 % during the experiment, the removals of total solids, total volatile solids, total suspended solids, volatile suspended solids, nitrogen, phosphorus, potassium and phenolic compounds were 57.3, 71.6, 26.5, 17.2, 35.7, 62.5, 49.5 and 55 % respectively. The cascade aeration proved to be an important alternative for composition the ARC treatment systems, with a view that is effective means of low cost and relatively fast for the aerobic treatment of organic material present in those wastewaters.